GP5 The immunogenetics and risk factors of pollinosis among russian children. case-control study. (June 2019) - Levina, Julia; Namazova-Baranova, Leyla; Savostyanov, Kirill; Pushkov, Alexander; Burdennyy, Alexey; Alekseeva, Anna; Efendieva, Kamilla; Vishneva, Elena
Abstract : Background and aim: Pollinosis is an allergic disease that manifests during spring or summer with symptoms of allergic rhinitis, conjunctivitis, asthma and atopic dermatitis. In Russia the most common reason for pollinosis is birch and grass pollen. Since pollinosis is a multifactorial disease, the aim of this study was to investigate the association between polymorphic markers of candidate genes and the development of the disease. Methods and patients: The genotypes of polymorphic markers of genes-candidates (IL4, IL4R, IL13, IL33, IL6, TLR4, MMP9) were examined by Real-time PCR for a group of 131 children 5–17 y.o. (average age 10.9, 81 boys and 50 girls) with pollinosis and for a control group of 78 healthy children. 86% of children with pollinosis had any family history of allergy, 58% had one allergic parent (33% - allergic mother, 25% - allergic father); 20% had both allergic parents; 51% had some family history of pollinosis. 75% of patients had atopic dermatitis while being toddlers. The average age of pollinosis debut was 4.9±2.8. The diagnosis of pollinosis was confirmed by the positive skin prick tests or by high level of specific IgE to tree or grass pollen in blood serum. Results: We reveal a statistically significant association of the rs1805010 of IL4R gene with pollinosis. The children with GG genotype of rs1805010 had increased risk of pollinosis compared with healthy controls (P = 0.010; OR = 3.73; 95% CI, 1.24 – 11.28). Moreover, there was a tendency to increase the allele C frequency of the rs1805015 of the IL4R gene in children with pollinosis (OR=1, 81, p=0, 040). No significant association was found with other polymorphisms. Conclusion: The results of the present study revealed an association of cytokine gene polymorphism IL4R rs1805010 with pollinosis. Our results indicate a high predictive value of this polymorphic marker for the development of pollinosis in Russian pediatric population.